Родина: поэзия / ред. Н. А. Русанова ; худож. О. А. Коняшин ; сост.: Ф. Пукроков, Н. А. Русанова ; авт. предисл. О. А. Поскребышев ; рец. О. А. Поскребышев - Русанова Н. А. (Удмуртия, 1982)
Экземпляры: Ф. 10 (20221213) / Инвентарный номер: 49544 / Цена: 1.20 / Авт.знак: Р60 / ББК: К84(2=411.2)6